2005
DOI: 10.1213/01.ane.0000144420.87770.fe
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Decreases the Convulsive Potency of Bupivacaine and Levobupivacaine in Rats: Involvement of α2-Adrenoceptor for Controlling Convulsions

Abstract: Dexmedetomidine, a highly selective alpha(2)-adrenoceptor agonist, is used in combination with local anesthetics for sedation and analgesia. We tested the hypothesis that dexmedetomidine used for sedation alters the convulsive potency of racemic bupivacaine and levobupivacaine in awake, spontaneously breathing rats. In the first experiments, male Sprague-Dawley rats were randomly divided into six groups: bupivacaine with no dexmedetomidine (bupivacaine control; BC), bupivacaine with small-dose dexmedetomidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Dexmedetomidine (doses of 10 and 100 μg/kg, but not one μg/kg) also reduced the seizure threshold during enflurane anesthesia in cats [20]. Anticonvulsant effects were shown by other investigators [21,22]. Dexmedetomidine (20 μg/kg followed by an infusion of one μg kg -1 min -1 ) increased the dose of cocaine required to cause seizures in Sprague-Dawley rats [21].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Dexmedetomidine (doses of 10 and 100 μg/kg, but not one μg/kg) also reduced the seizure threshold during enflurane anesthesia in cats [20]. Anticonvulsant effects were shown by other investigators [21,22]. Dexmedetomidine (20 μg/kg followed by an infusion of one μg kg -1 min -1 ) increased the dose of cocaine required to cause seizures in Sprague-Dawley rats [21].…”
Section: Discussionmentioning
confidence: 79%
“…With a cocaine infusion at 1.25 mg/kg per minute, rats treated with dexmedetomidine manifested seizures at 49.3 ± 14.8 minutes versus 25.0 ± 7.7 minutes in controls. In Sprague-Dawley rats, the dose of either levobupivacaine or bupivacaine required to induce seizures was higher in rats treated with dexmedetomidine than in controls [22].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was hypothesized that the reason for the excitatory phenomenon of myoclonus was a disequilibrium of the drug at the various effect sites in the central nervous system (CNS) [9,10]. Tanaka et al showed that dexmedetomidine administered for sedation reduced the convulsive potency of bupivacaine and levobupivacaine in awake, spontaneously breathing rats, probably by a 2 -adrenoceptor agonism [11]. Although myoclonus is thought not to be generated by an epileptic focus, dexmedetomidine, which acts to reduce the severity of convulsions, has not been previously investigated for myoclonus induced by etomidate.…”
Section: Introductionmentioning
confidence: 99%
“…Liver dysfunction may occur postoperatively in living-donor liver transplantation (LDLT) patients, as only 50% of the standard liver volume is usually transplanted to the recipient, and hypoperfusion and rejection of the graft or tissue can occur. Here we report the case of an LDLT previously reported method [7]. The lower limit of DEX quantitation was 50 pmol·ml −1 , and the intraassay and interassay variations were less than 8% throughout the range (50-5000 pmol·ml −1 ).…”
Section: Introductionmentioning
confidence: 77%